2013
DOI: 10.1186/1472-6947-13-61
|View full text |Cite
|
Sign up to set email alerts
|

The usability and preliminary effectiveness of a web-based physical activity intervention in patients with knee and/or hip osteoarthritis

Abstract: BackgroundA large proportion of patients with knee and/or hip osteoarthritis (OA) do not meet the recommended levels of physical activity (PA). Therefore, we developed a web-based intervention that provides a tailored PA program for patients with knee and/or hip OA, entitled Join2move. The intervention incorporates core principles of the behaviour graded activity theory (BGA). The aim of this study was to investigate the preliminary effectiveness, feasibility and acceptability of Join2move in patients with kne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 35 publications
2
43
0
Order By: Relevance
“…No results were found describing usability scales of other online or computerized dietary assessment tools. However, results from the SUS for a web-based physical activity intervention reported an average score of 73 (SD = 15), which is associated with 'good' usability [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No results were found describing usability scales of other online or computerized dietary assessment tools. However, results from the SUS for a web-based physical activity intervention reported an average score of 73 (SD = 15), which is associated with 'good' usability [29].…”
Section: Discussionmentioning
confidence: 99%
“…Although usability-testing has been used in various developed e-health software, such as smoking websites [28] and online physical activity tools [29], there is limited information published on the usability-testing of online dietary assessment websites [30]. Therefore, this study aims to identify usability and design issues associated with the completion of myfood24 (beta-version) and to determine tool acceptability among adolescents (11-18y) before and after making improvements (beta & live-version).…”
Section: Introductionmentioning
confidence: 99%
“…Seven of the 19 studies for which we calculated an effect size demonstrated small effects for pain intensity outcomes (d = 0.20 to 0.40) 38,43,44,53,55,57,58 and 8 of the 18 demonstrated small effect sizes for physical functioning outcomes (d = 0.20 to 0.40). 20,[39][40][41]47,51,54,55 Six of the studies had moderate effects, 2 for pain intensity (d = 0.64 to 0.72) 39,46 and 4 for physical functioning (d = 0.51 to 0.64).…”
Section: How Has the Internet Been Used For Treatment Of Chronic Noncmentioning
confidence: 97%
“…Several of the studies reported significant improvement in functioning and pain-related disability 17,20,21,25,37,42,44,46,[51][52][53]55 ; however, 10 studies 23,[38][39][40][41]43,45,47,57,58 did not find statistically significant improvement in physical functioning or disability in their intervention sample. At the 11-month follow-up assessment, Kristjansdottir et al 48 found a significant effect for the intervention condition in terms of physical functioning (FIQ) compared with baseline assessment; this effect was not seen at posttreatment in this sample.…”
Section: How Has the Internet Been Used For Treatment Of Chronic Noncmentioning
confidence: 97%
See 1 more Smart Citation